Business study mission to Thailand political environment, society, culture and values - Neo, Catherine Kiow Huay (2008)
This dissertation focuses primarily on the impact and future implications of the Asian financial crisis on Thailand's political environment, society, culture and values that may affect business investments in the short to medium term.